Right ventricular cardiac abscess secondary to traumatic osteomyelitis: Hematogenous dissemination from metaphysis to myocardium - Maitri Choudhary; Munesh Tomar (Wolters Kluwer Medknow Publications, 2021)
Background: A cardiac abscess is a suppurative infection involving cardiac tissues as myocardium, endocardium, and valves (native or prosthetic). The abscess could form as a direct extension of a preexisting cardiac focus such as bacterial endocarditis or from a distant septic focus leading to bacteremia. Clinical Description: We report an immunocompetent 3-year-old-child with a structurally normal heart presenting in septic shock secondary to right ventricle (RV) myocardial abscess. The abscess developed following hematogenous spread from neglected posttraumatic osteomyelitis of the left ankle and the causative organism was identified as methicillin sensitive Staphylococcus aureus. Management: Prompt action by a multidisciplinary team helped in reaching the diagnosis, effective management of septic shock, emergency open heart surgical removal of the septic mass, and concomitant lower limb arthrotomy saved the child from a bad outcome. Conclusion: This case reiterates the need for aggressive treatment of the open skeletal wound to prevent bacteremia and complications such as myocardial abscess. In a child presenting in septic shock, a quick point-of-care echocardiography is critical in ruling out possible underlying cardiac conditions such as bacterial endocarditis, myocardial abscess, or pericardial effusion. A high index of clinical suspicion is required to make a prompt diagnosis and aggressive medical and surgical intervention for good outcomes.